Work hard, play hard—The concept of playbour in Animal Crossing: New Horizons - Gemma Fantacci (Academy of Arts, University of Novi Sad, 2022)
Under the promise of complete creative expression, Animal Crossing: New Horizons (Nintendo, 2020), henceforth ACNH, has established one of the largest online communities— to date, more than 39 million copies have been sold—where players play to work and work to play within a visual and production ecosystem that influences the way the game is played and the customization choices. ACNH is based on a capitalist system: the environment can be exploited to obtain materials to create a variety of items; natural resources can be sold for bells (the main in-game currency) to buy and accumulate pieces of furniture; and, finally, players are strongly encouraged to go into financial debt to Tom Nook, the island manager, to create their dream island. The aim of this paper is to analyze the sugar-coated representation of the contemporary capitalist system of ACNH by investigating how Nintendo has exacerbated the concept of playbour (Kücklich, 2005)—a hybrid form that disguises work as play and capitalizes on the commodification of recreational activities, implementing neoliberal and capitalist logics into the core mechanics of the game. In so doing, it invites players to engage in ludic activities that appropriate the principles of the gig economy and the platform economy (Jarrett, 2022) to persuade them to earn bells, purchase items, and get further into debt. Lastly, the paper will present a parallelism with the early simulation games, Capitalism, Sim City, Railroad Corporation, and Tycoon, which are explicitly classified as business management games, and the neoliberal dynamics of ACNH, cleverly disguised through a specific marketing campaign that positions the game among the so-called cozy games, that is to say, games in which the ludic action is synonymous with self-care. Beyond a kawaii design, are capitalist and neoliberal dynamics that normalize the fetishization of goods and the exploitation of natural resources for profit.